Mapping Tendencies in Curriculum Research on Physical Education and Sports: A Bibliometric Analysis - Şahin, Aykut; Karakaya, Yunus Emre; Dikmen, Melih (Ozgen Korkmaz, 2023)
This study aims to investigate previous curriculum research on physical education and sports using the bibliometric mapping method. A systematic map was created for the research tendencies in physical education and sports curricula studies conducted between 1975 and 2021. Accordingly, the intention is to fill a gap in the literature by conducting a general situation analysis about the present status of curriculum studies in physical education and sports based on the publication and citation data obtained from the Web of Science (WoS) database. The software VOSviewer was utilised for the bibliometric analysis. After scanning the studies in the database, 454 studies were accessed at the initial stage. A total of 114 studies were covered in the analysis by following certain exclusion criteria. The findings suggested that curriculum studies in physical education and sports were conducted in association with numerous multidisciplinary research areas. Furthermore, in recent years, a linear increase in curriculum studies has occurred on this subject matter. It was also found that scientists from universities in the United States of America were at the centre of the studies. Another striking result was the limited number of journals specialising in sports and education. The results of the bibliometric maps also demonstrated that the researchers in this field investigated a variety of subjects that can be grouped under four main disciplines: ‘health and physical education,’ ‘curriculum reform,’ ‘contents,’ and ‘pre-service teachers.’ Addedl the results revealed that studies on physical education and sports curricula were conducted with a focus on current developments. © 2023, Ozgen Korkmaz. All rights reserved.
Keywords: bibliometric analysis; curriculum; physical education; sports